2014
DOI: 10.1093/molbev/msu234
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Evolutionary and Functional Tests of Adaptive Hypotheses: A Case Study of Altitudinal Differentiation in Hemoglobin Function in an Andean Sparrow, Zonotrichia capensis

Abstract: In air-breathing vertebrates, the physiologically optimal blood-O2 affinity is jointly determined by the prevailing partial pressure of atmospheric O2, the efficacy of pulmonary O2 transfer, and internal metabolic demands. Consequently, genetic variation in the oxygenation properties of hemoglobin (Hb) may be subject to spatially varying selection in species with broad elevational distributions. Here we report the results of a combined functional and evolutionary analysis of Hb polymorphism in the rufous-colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 80 publications
6
58
0
4
Order By: Relevance
“…For example, birds typically express two main Hb isoforms in definitive red blood cells -a major isoform, HbA, which incorporates α-type products of the α A -globin gene, and a minor isoform, HbD, which incorporates α-type products of the α D -globin gene; the two isoforms share the same β-type subunits Grispo et al, 2012;Opazo et al, 2015). In all bird species that have been examined to date, the minor HbD isoform has an appreciably higher O 2 affinity than the major HbA isoform in the presence of allosteric effectors (Grispo et al, 2012;Projecto-Garcia et al, 2013;Cheviron et al, 2014;Galen et al, 2015;Natarajan et al, 2015bNatarajan et al, , 2016. Other sauropsid taxa also tend to co-express multiple, structurally distinct Hb isoforms in definitive erythrocytes (Weber and Jensen, 1988;Storz et al, 2011bStorz et al, , 2015bDamsgaard et al, 2013).…”
Section: Heterotropic Allosterymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, birds typically express two main Hb isoforms in definitive red blood cells -a major isoform, HbA, which incorporates α-type products of the α A -globin gene, and a minor isoform, HbD, which incorporates α-type products of the α D -globin gene; the two isoforms share the same β-type subunits Grispo et al, 2012;Opazo et al, 2015). In all bird species that have been examined to date, the minor HbD isoform has an appreciably higher O 2 affinity than the major HbA isoform in the presence of allosteric effectors (Grispo et al, 2012;Projecto-Garcia et al, 2013;Cheviron et al, 2014;Galen et al, 2015;Natarajan et al, 2015bNatarajan et al, , 2016. Other sauropsid taxa also tend to co-express multiple, structurally distinct Hb isoforms in definitive erythrocytes (Weber and Jensen, 1988;Storz et al, 2011bStorz et al, , 2015bDamsgaard et al, 2013).…”
Section: Heterotropic Allosterymentioning
confidence: 99%
“…As in the case with the mammals, the 29 pairwise comparisons are phylogenetically independent. For information regarding elevational ranges, see Projecto-Garcia et al (2013), Cheviron et al (2014), Galen et al (2015) and Natarajan et al (2015bNatarajan et al ( , 2016.…”
Section: The Importance Of Accounting For Phylogenetic Historymentioning
confidence: 99%
See 1 more Smart Citation
“…This result, together with functional analyses (Natarajan et al., 2015) suggest that a Thr/Ser‐69 substitution arising de novo did not facilitate the colonization of high‐elevation environments by Ruddy Ducks, implying that the previously proposed evolutionary scenario requires reevaluation. Other studies have revealed that patterns of elevational differentiation in hemoglobin sequences consistent with spatially variable selection need not imply adaptive evolution because amino acid replacements may have no effect on respiratory properties of hemoglobin isoforms (Cheviron et al., 2014). However, we note that recent analyses indicate that Ruddy Ducks throughout their range, including North America, possess hemoglobin with relatively high O 2 affinity, similar to other Andean species (Natarajan et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed results from genome scans increasingly reveal signals of selection acting on physiological processes (Akey et al., 2010; Gautier et al., 2009; Shimada, Shikano, & Merilä, 2011; Simonson et al., 2010), and on metabolism in particular (reviewed in Marden, 2013). While these types of studies can provide initial evidence in support of adaptive divergence, the case of the Andean Sparrow ( Zonotrichia capensis ) highlights their potential limitations: A genome scan suggested selection acting on metabolic pathways, but this result was contradicted by experimental tests of associated enzyme affinity (Cheviron et al., 2014). Thus, direct measures of physiological processes are integral in the context of studying putative adaptive divergence.…”
Section: Introductionmentioning
confidence: 99%